Lichen sclerosus et atrophicus and Borrelia burgdorferi infection. - Trevisan, G.; Menni, S.; Stinco, G.; Nobile, C.; Pistritto, G.; Perin, R.; Stanta, G. (European Journal of Pediatric Dermatology, 2018)
Lichen sclerosus et atrophicus (LSA) is a chronic dermatosis of unknown etiology. The possible rclationship between Lyme disease and LSA has been suggested by the identification of borrelial organisms in histological sections and recently by DNA amplification using polymerase chain reaction (PCR). In the present study 7 females, aged 6 to 16 years (mean age: 9.9), with LSA were investigated by PCR analysis. Four patients lived in a non-endemic area (Milan) and 3 patients in an endemic area (Trieste). Antibodies against Borrelia burgdorferi could be detected in 3 out of 6 patients (IgG titer ranging from 1:128 to 1:256). The DNA of Borrelia was detected in all the patients living in Trieste. These results confirm that Borrelia burgdorferi may be an etiological agent of LSA, although LSA must be considered a multifactorial disease. In the Authors’ opinion it is possible that infection with only some strains of Borrelia burgdorferi leads to LSA and this may explain the conflicting data gathered from different regions.